Leadership and management development within the NHS: a phenomenological and critical account - Gallagher-Read, Mark John (2019)
Regarding the failures of Mid Staffordshire NHS Foundation Trust between 2005 and 2009, Sir Robert Francis QC commented to the then Secretary of State for Health ‘that above all, it failed to tackle an insidious negative culture involving a tolerance of poor standards and a disengagement of managerial and leadership responsibilities’ (The Francis Report, 2013, p. 9). This was a criticism directly laid at the feet of those NHS leaders and managers who were charged with caring for vulnerable families and friends during that time. Understanding how leaders and managers are developed within the NHS is of a notable concern, especially if we wish not to see the likes of what occurred at Stafford Hospital again. Even after significant investment in NHS management training, Lake (2016) of the NHS Leadership Academy suggests that there are still vague barriers which prevent a culture of effective leadership development from embedding itself within the NHS workforce. This view is supported by others including Ahmed et al. (2015), West et al. (2015) and Tull (2018). It can be reasonably asserted that this unclear picture starts with a need to explore the recent experiences of NHS staff who have been participants on NHS leadership and management development (LMD) trainings.